The influence of debt policy, dividend policy and profitability on the value of Manufacturing Companies in Indonesia for the 2018-2022 - Natasya Ayu u Andira; Imronudin Imronudin; Nur Achmad (Institute of Computer Science (IOCS), 2024)
This study's goal to examine the debt policy, dividend policy, and profitability of Indonesian Stock Exchange-listed manufacturing companies from 2018 to 2022. The type of research methodology used in this research is quantitative research. The data used in this research is secondary data, namely financial reports of manufacturing companies. The research sample consisted of 32 companies listed on the Indonesian Stock Exchange. Purposive sampling is the sampling method used in this research. Data analyzed from the idx.co.id page. The observation period for this research is from 2018-2022. The data that has been collected is analyzed using multiple regression analysis. Based on the data analysis carried out, it is concluded that debt management (DER) does not have a positive or significant influence on manufacturing company value (PBV). Then the dividend policy (DPR) and profitability (ROA) variables have a positive and significant influence on the company value (PBV) of manufacturers listed from 2018 to 2022 on the Indonesian Stock Exchange